Intelligent control of nitrogen laser - Tan, Siong Chai. (2008)
The aim is to apply computational intelligence in stabilizing some output parameters of a nitrogen laser beam. The scope includes explore and implement fuzzy logic algorithms to trol of the output characteristics, explore the use of neutral network control and comparing with using fuzzy logic control.